Bandwidth assessment of scheduled and unscheduled communication in hybrid networked control system. Issue 4 (2nd October 2022) - Azad, S M A K; Kannan, Srinivasan
ABSTRACT: The large integrated industrial applications require unified communication to combine data from multiple domains forming a hybrid network. The scheduling of network access time to multi-domain data in an industrial hybrid network is a challenging task. This paper extends the contribution of the network model mentioned in the literature to assess the bandwidth of both the scheduled and unscheduled communication in hybrid networked control systems. This paper's contribution includes four phases as follows: a) simulation of a hybrid networked control system (h-NCS) consists of four domains with different bandwidth allocations for an application of transmitting a data packet over a network stack from wired node to the wireless node. b) the mathematical demonstration of TCP and IEEE802.11b related to domains incorporated in h-NCS for data transmission. c) the normalisation of the bandwidth of the network access time for both scheduled and unscheduled data packets of h-NCS by implementing Dempster's rule of combination. d) comparison analysis of proposed h-NCS with the traditional NCS for network access time utilised by both the scheduled and unscheduled data transmission.